Making space : merging theory and practice in adult education - Sheared, Vanessa, 1956-; Sissel, Peggy A. (Westport, CT : Bergin & Garvey, 2001)
Annotation A study of the sociological and political implications of adult education and adult learning theories and practices through the lens of race, class, gender, language, culture, and sexual orientation.
Annotation Building on new, emerging perspectives, Making Space examines the phenomenon of adult learning through multiple voices and promotes a critical analysis of the functions, structures, and activities that have perpetuated the silence and invisibility of marginalized groups in the field of adult education.
Foreword / Phyllis M. Cunningham -- Opening the gates : reflections on power, hegemony, language, and the status quo / Peggy A. Sissel, Vanessa Sheared -- Incorporating postmodernist perspectives into adult education / David F. Hemphill -- Challenging adult learning : a feminist perspective / Daniele D. Flannery, Elisabeth Hayes -- Talking about whiteness : "adult learning principles" and the invisible norm / Sue Shore -- An invisible presence, silenced voices : African Americans in the adult education professoriate / Sherwood E. Smith, Scipio A.J. Colin III -- The African American market woman : her past, our future / Cheryl A. Smith -- Creating an intellectual basis for friendship : practice and politics in a white women's study group / Jane M. Hugo -- Northern philanthropy's ideological influence on African American adult education in the rural south / Bernadine S. Chapman -- Struggling to learn, learning to struggle : workers, workplace learning, and the emergence of human resource development / Fred M. Schied -- The role of adult education in workplace ageism / Su fen Liu, Frances Rees -- Communities in the classroom : critical reflections on adult education in an Appalachian community / Mary Beth Bingman, Connie White with Amelia R.B. Kirby -- Education, incarceration, and the marginalization of women / Irene C. Baird -- Adult basic education : equipped for the future or for failure? / Donna Amstutz -- Teaching as political practice / Ruth Bounous -- African American women of inspiration / Angela Humphrey Brown -- Through the eyes of a Latina : professional women in adult education / Rosita Lopez Marcano -- By my own eyes : a story of learning and culture / Lynette Harper, "Mira" -- Using queer cultural studies to transgress adult educational space / Andre P. Grace -- Feminist perspectives on adult education : constantly shifting identities in constantly changing times / Elizabeth J. Tisdell -- Between a rock and a hard place : confronting who "we" are / Merilyn Childs -- Technologies of learning and work : disciplining the self / John Garrick, Nicky Solomon -- The political economy of adult education : implications for practice / Jorge Jeria -- What does research, resistance, and inclusion mean for adult education practice? A reflective response / Vanessa Sheared, Peggy A. Sissel.
Includes bibliographical references and index.
Electronic reproduction.
Master and use copy. Digital master created according to Benchmark for Faithful Digital Reproductions of Monographs and Serials, Version 1. Digital Library Federation, December 2002.
digitized
Print version record.
English.
Keywords: Adult education -- Social aspects -- United States; Discrimination in education -- United States; Critical pedagogy -- United States; Éducation des adultes -- Aspect social -- États-Unis.; Discrimination en éducation -- États-Unis.; Pédagogie critique -- États-Unis.; EDUCATION -- Adult & Continuing Education; EDUCATION -- Non-Formal Education; Adult education -- Social aspects; Critical pedagogy; Discrimination in education; United States; Aufsatzsammlung; Erwachsenenbildung; Rassismus; Sexismus; USA